Investigation of C-C bond formation mediated by bombyx mori silk fibroin materials - Kuehbeck, Dennis; Ghosh, Munmun; Sen Gupta, Sayam; Diaz, David Diaz (ACS Sustainable Chemistry & Engineering, 2014)
The formation of C-C bonds is a prerequisite for all life on earth. Understanding the role of proteins in mediating the formation of these bonds is important for understanding biological mechanisms in evolution, as well as for designing ``green catalysts''. In this work, the ability of silk fibroin (SF) proteins to mediate selective C-C bond formation under mild conditions was comprehensively evaluated and compared between different SF-based materials and other proteins. Aqueous SF solution (ASFS), freeze-dried SF (FDSF), mesoporous SF (MPSF), and SF hydrogel (SFHG) materials were prepared and characterized by a variety of techniques including, among others, FE-SEM, ICP-OES, FT-IR, and TGA. The nitroaldol (Henry) reaction, Knoevenagel condensation, and direct aldol reaction were used as models for this study, in which the recovery and reusability of the protein was also evaluated.
Keywords: Aldol-like reactions; C-C Bond formation; Knoevenagel condensation; Proteins; Silk fibroin